Impact analysis of functionally-graded graphene nanoplatelets-reinforced composite plates laying on Winkler-Pasternak elastic foundations applying a meshless approach. (15th August 2021) - Selim, B.A.; Liu, Zishun
Highlights: Impact of graphene reinforced composite plates on elastic foundations is studied. An element-free approach based on the higher-order shear deformation theory is used. The effective Young's modulus is calculated by using the modified Halpin-Tsai model. The modified nonlinear Hertz contact law is used for calculating the contact force. The effects of changing different parameters on the impact results are examined. Abstract: In this paper, we investigated impact analysis of functionally-graded (FG) graphene nanoplatelets (GPLs)-reinforced composite plates with arbitrary boundary conditions and resting on Winkler-Pasternak elastic foundations. The element-free improved moving least-squares Ritz (IMLS-Ritz) approach and the higher-order shear deformation theory (HSDT) are used to develop the theoretical formulation. Target plates are set to have uniform and functionally graded GPLs distributions throughout their thickness. The modified Halpin-Tsai model is considered to calculate the effective Young's modulus yet the rule of mixture is used to calculate the effective Poisson's ratio and mass density. The modified nonlinear Hertz contact law is adopted to describe the contact force between the spherical impactor and target plates. In addition, Newmark time-integration method is employed to obtain dynamic response of plates as well as impactor's displacement. An extensive parametric study is performed to examine effects of some essential parameters on results (distributions and volume fraction of GPLs, initial velocity and radius of impactor, plate's width-to-thickness ratio, Winkler and Pasternak modulus parameters as well as boundary conditions).